The Domestic Politics of Humanitarian Intervention: Public Opinion, Partisanship, and Ideology. Issue 3 (3rd July 2012) - Hildebrandt, Timothy; Hillebrecht, Courtney; Holm, Peter M.; Pevehouse, Jon
Abstract : The debate around humanitarian intervention and the responsibility to protect generally concerns a collective action problem on the international level: motivating states to participate in a multilateral coalition to stop a mass atrocity. This debate presupposes that states enjoy a domestic consensus about their rights and responsibilities to intervene. This article reconsiders this assumption and examines the sources of domestic political will for intervention, particularly the role of partisanship, ideology, and public opinion on Congressional members' willingness to support US intervention for humanitarian purposes. We analyze several Congressional votes relevant to four episodes of US humanitarian intervention: Somalia, Haiti, Bosnia, and Kosovo. We find that public support for humanitarian intervention increases Congressional support and that other political demands, primarily partisanship and ideological distance from the president, often trump the normative exigencies of intervention. Our findings shed light on the domestic political dynamics behind humanitarian intervention and can help explain why some recent humanitarian missions have proceeded without seeking Congressional approval.